Respon Ulama Maskumambang atas Gerakan Wahabi 1922-1961: Pemikiran Kiai Muhammad Faqih dan Kiai Ammar Faqih - Faridatul Hidayatul Mahiroh (Qurthuba: The Journal of History and Islamic Civilization, 2019)
Abstract: This article examines the comparative views of two scholars from Gresik regarding the Wahhabi movement. The focus of the discussion is: 1) How is the biography and thoughts of KH. Muhammad Faqih in response to the Wahhabi movement 2) What is the biography and thoughts of KH. Ammar Faqih in response to the Wahhabi movement 3) What are the differences and similarities between KH. Muhammad Faqih and KH. Ammar Faqih in response to the Wahhabi movement. This article uses a historical approach and a sociology of knowledge approach. This study uses the theory of Symbolic Interactionism according to Herbert Blumer. The method used is the historical method: heuristics, criticism, interpretation, historiography. The results of this study indicate that: 1) KH. Muhammad Faqih (1857-1937 AD) was the fourth child of KH. Abdul Djabbar and Nyai Nursimah. KH's thoughts. Muhammad Faqih is very counter to the thoughts of Muhammad bin Abdul Wahhab 2). KH. Ammar Faqih (1902-1965 AD) was the fifth child of KH. Muhammad Faqih and Nyai Nur Khodijah. KH's thoughts. Ammar is very pro with the thoughts of Muhammad bin Abdul Wahhab 3) The difference between the two is that KH. Muhammad Faqih allows tawassul with people who have died but KH. Ammar Faqih prohibits tawassul with people who have died. KH. Muhammad Faqih also allowed reading the Prophet's blessings either aloud or quietly but KH. Ammar forbade reciting salawat aloud while the similarity is that both of them allow salawat and visiting the graves. Keywords: kiai, comparative, thought, Wahabi